Spin-orbit coupling in the superconducting phase and DDW states of high-T-c cuprates - Ghosh, Angsula [UNESP] (Springer, 2010)
The effects of the spin-orbit coupling are considered for the high T (c) cuprates with asymmetric superconducting gap (SC) and the d-density wave (DDW) phase due to its vital role in the experimental determination of the DDW state. Experiments predict an anisotropy in the DSC gap where |Delta(0,pi)|>|Delta(pi,0)| and the gap node deviates from the diagonal direction towards the k (x) axis. Measurements also demonstrate DDW to be a possible candidate for the pseudogap in the underdoped phase. Due to the spin-orbit (SO) coupling in the low temperature orthorhombic (LTO) phase, the phase diagram of the cuprates suffers a change due to the modification of the T* value, the temperature characteristic of pseudogap, although T (c) remains unaltered. Moreover, for a more generalized SO coupling, the DDW gap decreases with the angle but has no effect on the SC gap. We calculate the density of states in the various regimes of doping for the mixed SC+DDW states in the underdoped (UD) phase, SC state in the overdoped phase and also the DDW state in the UD phase and compare them with various theoretical and experimental works. The temperature dependence of the specific heat does not exhibit any qualitative change due to the SO coupling.